Analyzing Islamic Boarding School Students’ Scientific Literacy Skills on Physics Material - Zulistina, Haniel; Sunarti, Titin (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
The purpose of this research was to analyze Islamic boarding school students’ scientific literacy skills. The research used descriptive quantitative method. The research was conducted at the Islamic Boarding School in Jombang namely, SMA 1 Darul Ulum Unggulan BPPT. The research sample consisted of 51 students from class XI IPA. Data was collected using research instruments in the form of literacy tests on aspects of competence. The scientific literacy test instrument contains 14 questions about the description of physics materials that have been validated by three expert lecturers. The research results competence aspect was still in low category with an average 31.2. The research also found that the scientific literacy of Islamic boarding school students was still in the low category, with an average score of 35.7. The average score of scientific literacy for female students is 37.5 and for male students it is 35.1. All Islamic boarding schools are expected to implement and support activities that are useful for developing scientific literacy skills.